(Digital) Activism at the Interstices: Anarchist and Self-Organizing Movements in Greece - Eugenia Siapera; Michael Theodosiadis (tripleC: Communication, Capitalism & Critique)
The paper traces the history and evolution of the anarchist and self-organising movements in Greece, paying attention to their communicative practices and their implications for political praxis. After years of repression, and following the hegemony of the social democratic Pasok, and subsequently Syriza, the movements are currently coming to their own. Beginning with a brief history of the movements and more broadly of the left in Greece, the paper focuses on the current moment, determined by three events: the revolt of 2008, the movement of the squares in 2011, and the rise and u-turn of Syriza in 2015. Examining the critiques, discourses and communicative practices of the antagonistic movement as a whole, the paper argues that these constitute an alternative path to organizing beyond populist hegemony. Equally, the antagonistc movement tries to eschew the problems associated with the so-called folk politics, by paying attention to the growth of the movement through combining affect and experience, new learning and action, and through ultimately contributing to fundamental shifts in political subjectivities.